Pulmonary valve regurgitation following balloon valvuloplasty for pulmonary valve stenosis: Single center experience - Asim Yousuf Al Balushi; Hamood Al Shuaili; Murtadha Al Khabori; Salim Al Maskri (Wolters Kluwer Medknow Publications, 2013)
Background: Pulmonary valve regurgitation following balloon valvuloplasty for moderate to severe pulmonary valve stenosis is a known late outcome of this procedure. Objective: The aim of the study was to characterise the status of pulmonary regurgitation on follow up after pulmonary valve balloon dilatation (PVBD), and to study the determinant of the severity of PR. Materials and Methods: We retrospectively reviewed 50 consecutive patients, aged 2 days to 18 years, with isolated pulmonary valve stenosis, who had undergone PVBD in 2004-2009 and were assessed with follow-up Doppler echocardiography. The impact of balloon to annulus ratio, age, and valve anatomy on the late development of moderate and severe pulmonary valve regurgitation following balloon valvuloplasty was analysed. Results: Six patients (12%) had no pulmonary valve regurgitation; 32 (64%) had mild, 9 (18%) had moderate, and 3 (6%) had severe pulmonary valve regurgitation at a mean follow-up of 4 years. Balloon to annulus ratio, age, and valve anatomy were not statistically significant predictors for moderate and severe pulmonary valve regurgitation. Conclusions: The majority of patients in our population had mild pulmonary valve regurgitation. Moderate to severe pulmonary valve regurgitation was well tolerated at midterm follow-up. Age, balloon to annulus ratio, and valve anatomy were not statistically significant predictors for the late development of moderate and severe valve regurgitation. Large and longer follow-up studies are needed to address this question.